The impact of metabolic syndrome on hepatocellular carcinoma: a mendelian randomization study - Chendong Yuan; Xufeng Shu; Xiaoqiang Wang; Wenzheng Chen; Xin Li; Wenguang Pei; Xujie Su; Zhenzhen Hu; Zhigang Jie (Scientific Reports)
Abstract Traditional epidemiological studies are susceptible to confounding factors. To clarify the impact of metabolic syndrome and its diagnostic components on hepatocellular carcinoma, we conducted a preliminary mendelian randomization analysis with metabolic syndrome and its diagnostic components as exposures and hepatocellular carcinoma as the outcome. Another set of genetic data related to hepatocellular carcinoma was used as a validation cohort, repeating the mendelian randomization analysis and combining the two groups for a meta-analysis. Preliminary analysis showed that metabolic syndrome (P-value = 0.002) and waist circumference (P-value = 0.026) are significantly positively correlated with an increased risk of hepatocellular carcinoma. After multiple testing corrections, metabolic syndrome (PFDR-value = 0.013) remained significant, although the association between waist circumference (PFDR-value = 0.079) and hepatocellular carcinoma was considered suggestive, the meta-analysis further confirmed the impact of metabolic syndrome (P-value = 0.0002) and waist circumference (P-value = 0.0038) in increasing the risk of hepatocellular carcinoma. After adjusting for the genetic predictive effects of all exposures, waist circumference was found to be a key factor significantly influencing the relationship between metabolic syndrome and hepatocellular carcinoma. In summary, our study indicates that metabolic syndrome increases the risk of hepatocellular carcinoma, particularly among individuals with a larger waist circumference.